Analisis Pengaruh Produk Domestik Regional Bruto dan Jumlah Penduduk Terhadap Tingkat Kemiskinan di Kabupaten Nagan Raya - Yayuk Eko Wahyuningsih; Zamzami Zamzami (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
The objective of the study is to analyse the effect of gross regional domestic products (GRDP) and population on the rate of povery in Nagan Raya. The model utilized in the study was a log multiple regression model. Secondary data from BPS were used to test the selected model. The results of study showed that all independent variabels have statistically significant impact on the rate of poverty. The direction of the two variables was also consistent to the theory where the GRDP and population have negative relation to the rate of poverty. The t and F tests also confirmed that both individually and overall the independent variabels have significant impact on the rate of poverty. The coefficient of determination is 0.96 meaning that 96 percent of variation in the independent variabels can be used to explan the variation of the rate of poverty while the rest will be of other variables which are not included in the model.